MONETARY POLICY: COMPARISON OF MASUDUL ALAM CHOUDHURY AND MILTON FRIEDMAN ECONOMIC THOUGHT - Faisal Affandi (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
This study aims; 1) to describe Masudul Alam Choudhury and Milton Friedman version of monetary policy, 2) to describe the comparison of Masudul Alam Choudhury and Milton Friedman thoughts on monetary policy, 3) to describe the relevance of Masudul Alam Choudhury and Milton Friedman version of monetary policy to monetary policy in Indonesia. The research method used is a qualitative method with a literature review type. The results showed that; 1) Choudhury put forward the endogenous theory of money in Islam, where the central bank as the monetary authority only facilitates the circulation of the money supply volume so that the amount is accordance with actual spending and not spending demand expectation, 2) Friedman argues that money only affects inflation and does not affect economic growth, therefore monetary policy must be directed only affects at controlling inflation and not directed at influencing real economic activity, 3) The relevance of Choudhury and Friedman economic thinking regarding monetary policy on monetary policy in Indonesia can be seen from the implementation monetary policy implemented by Bank Indonesia. Keywords: Monetary Policy, MA Choudhury, M. Friedman.